Generalized analysis of a dust collapse in effective loop quantum gravity: Fate of shocks and covariance - Giesel, Kristina; Liu, Hongguang; Singh, Parampreet; Weigl, Stefan (Physical Review D, 2024)
Based on modifications inspired from loop quantum gravity (LQG), spherically symmetric models have recently been explored to understand the resolution of classical singularities and the fate of the spacetime beyond. While such phenomenological studies have provided useful insights, questions remain on whether such models exhibit some of the desired properties such as consistent LTB conditions, covariance, and compatibility with the improved dynamics of loop quantum cosmology in the cosmological and LTB sector. We provide a systematic procedure to construct effective spherically symmetric models encoding LQG modifications as a 1+1 field theory models encoding these properties following the analysis in our companion paper [K. Giesel et al., Embedding generalized LTB models in polymerized spherically symmetric spacetimes, Phys. Rev. D 110, 104017 (2024)PRVDAQ2470-001010.1103/PhysRevD.110.104017]. As concrete examples of our generalized strategy, we obtain and compare with different phenomenological models, which have been investigated recently and demonstrate resolution of singularity by quantum geometry effects via a bounce. These include models with areal gauge fixing, a polymerized vacuum solution, polymerized junction conditions, and an Oppenheimer-Snyder dust collapse model. An important insight from our approach is that the dynamical equations care about the det(e) part rather than the square root of the determinant of the spatial metric. As a result, shock solutions that have been argued to exist in some models are found to be absent even if one considers coordinate transformations.
CRIS-Team Scopus Importer:2025-02-04